Random room mobility model and extra‐wireless body area network communication in hospital buildings. Issue 1 (1st January 2015) - Misra, Sudip; Mahapatro, Judhistir; Mahadevappa, Manjunatha; Islam, Nabiul
Abstract : Wireless body area networks (WBANs) can help in enabling efficient patient monitoring solution for ubiquitous healthcare. Communication in WBANs is undertaken in two phases: intra‐WBAN and extra‐WBAN . The prevailing WBANs use cellular network or WiFi in the extra‐WBAN phase involving communication between the on‐body coordinator and access points (APs) connected to the medical server through the internet. The medical applications of the WBANs have stringent requirements of low end‐to‐end delay and high packet delivery ratio. The authors evaluate the performance of extra‐WBAN communication in the network of WBANs which is deployed within a building environment. They proposed a mobility model named random room mobility ( RRM ), which is used to capture the dynamics of WBAN user mobility within the building. They studied the performance of extra‐WBAN communication using the proposed mobility model and a random waypoint mobility model. The metrics used in evaluating the performance are packet drop ratio, average node‐to‐AP delay and average residual energy per node. The authors show that with an increase in the number of WBANs, the traffic generation rate and the payload size have high impact on the packet loss in the network. They studied the performance of extra‐WBAN communication using the priority mode available in IEEE 802.11 for provisioning quality‐of‐service (QoS). We show that it is suitable for medical applications, when the size of network consisting of WBANs, including the QoS‐enabled WBANs, is small.